Identification of 1,25-Dihydroxycholecalciferol, a Form of Vitamin D(3) Metabolically Active in the Intestine - Holick, M. F. (1971)
A biologically active vitamin D(3) metabolite (“peak V metabolite”) more polar than 25-hydroxycholecalciferol has been isolated from chicken intestines in pure form as a mono(trimethylsilyl)ether derivative. The molecule has been identified as 1,25-dihydroxycholecalciferol by means of mass spectrometry, ultraviolet absorption spectrophotometry, and specific chemical reactions.